FINE ARTS AND FOLK CULTURE INCLUDED IN INDIAN PAINTING: भारतीय चित्रकला में ललित कला व लोक संस्कृति का समावेश - Kumari, Kanchan (International Journal of Research -GRANTHAALAYAH, 2017)
India is an ancient cultural country. Art is a product of human culture. Its rise is reflective of the beauty of man. The unique fusion of folk art is seen in the art and culture here. Many scholars have periodically stated the importance of folk art. Folk art is a mirror of folk tradition culture in our country. Which can be seen in various rituals. Folk art can be seen in various forms in different provinces like India. Which is known by various names. Although these useful items of daily life were not made with the goal of fine arts, yet the end of the art of collective life is visible to us and it is not wrong to call them artistic objects. Along with the development of civilization, man did not leave a useful notion in his manufactured goods, but by his fluidity his fluidity made him beautiful product for fine arts in some quantity. भारत एक प्राचीन सांस्कृतिक देश है। कला मानव संस्कृति की उपज है। इसका उदय मानव की सौन्दर्य भावना का परिचायक है। यहाँ की कला एवं संस्कृति में लोककला का अनूठा समन्वय दिखाई देता है। अनेक विद्वानों ने समय-समय पर लोककला के महत्त्व को बताया है। लोककलाऐं हमारे देश में लोक परम्पराओं संस्कृति का दर्पण है। जो विभिन्न रीति रिवाज उत्सव में देखे जा सकते है। भारत जैसें देश में विभिन्न प्रान्तों में विविध रूपों में लोककला देखी जा सकती है। जो विभिन्न नामों से जानी जाती है। दैनिक जीवन की इन उपयोगी वस्तुओं का निर्माण यद्यपि ललित कला के लक्ष्य से नहीं हुआ, तथापि सामूहिक जीवन की कलाप्रियता का अंष हमें इसमें दृष्टिगोचर होता है और इन्हें कलात्मक वस्तुएँ कहे तो गलत नहीं होगा। सभ्यता के विकास के साथ-साथ मानव ने अपनी निर्मित वस्तुओं में उपयोगी धारणा को नहीं छोड़ा परन्तु उसकी कलाप्रियता ने अपनी प्रवाहशीलता द्वारा कुछ मात्रा में उन्हें ललित कला के लिये सुन्दर उपादान बना दिया।